Study guides

☆☆

Q: What is 6x X 9x?

Write your answer...

Submit

Still have questions?

Related questions

If: 9x+7 = 6x+25 Then: x = 6

x + 2x + 6x = 9x

9x-11 = 6x+1 9x-6x = 1+11 3x = 12 x = 4

6x + 47 = 9x + 11 6x + 36 = 9x 36 = 3x 12 = x

9x+6 = 6x+15 9x-6x = 15-6 3x = 9 x = 3

it's an easy one :)-6 - 6x = 9 - 9x-6x + 9x = 9 + 63x = 15x = 15/3X = 5

9x-19=6x+2 so 3x=21 and x=7

9x + 8 = 6x + 20(- 8 from both sides)9x = 6x + 12(- 6x from both sides)3x = 12(divide both sides by 3)x = 4

9x - 3(x + 13y) = 9x - 3x - 39y = 6x - 39y = 3(2x - 13y)

That is an equation.Oh, you wanted to know for which values of x that equation is true? Okay...6x + 3x + 8 = 35⇔ (6x + 3x) + 8 = 35⇔ 9x + 8 = 35⇔ 9x + 8 - 8 = 35 - 8⇔ 9x + 0 = 27⇔ 9x = 27⇔ 9x / 9 = 27 / 9⇔ x = 27 / 9⇔ x = 3

The GCF of 6x and 9x is 3x

3x + 6x +1 = 10 9x = 10 - 1 9x = 9 x = 1

24 ; Identify the variable in the equation.5 + 9x = 68a. 5 b. 68 c. x d. 9x

This simplifies to 6x = -3, so x = -0.5 Check: (3 x -0.5) + 2 = (9 x -0.5) + 5 ie -1.5 + 2 = -4.5 + 5 0.5 = 0.5 QED3x + 2 = 9x + 5 3x - 9x + 2 - 2 = 9x - 9x + 5 - 2-6x = 3 -6x/-6 = 3/-6 x = -1/2 or x = -0.5

3x. 15x - 9x = 6x 9x - 6x = 3x 6x - 3x = 3x 3x - 3x = 0

In this equation, x=6.

Yes it can be solved and X=0.

3(x + 1)(2x + 1)

3x + 6x = 9x

The equation you gave (-9x - 36 = 6x) does not have y included anywhere. Assuming you meant that -9x - 36 = 6x + y: Step 1: Give y its own side: -9x - 36 -6x = 6x - 6x + y -15x -36 = y Step 2: Set x as 0 -15(0) - 36 = y y = -36 The y-intercept is -36

9x + 3 - 6x - 2 = 3x + 1

-3x+9x can be simplified to 6x

12

(6x^3-9x^2) / (2x-3) = 3x^2((2x-3) / (2x-3) = 3 x ^2 (3 x squared)

6x+11=92-3x +3x +3x 9x+11=92 -11 -11 9x=81 divide by 9 x=9